The essences of unity in cultural diversity: an analytical review on prophet’s farewell address - Shogar, Ibrahim (Universiti Sains Islam Malaysia (USIM) Press, 2020)
Appreciating goals of the United Nations and emphasizing its role, the global community is currently united by the outbreak of COVID-19 pandemic in many aspects. Close cooperation between countries and helpful assistance between communities are taking place among the different nations regardless of their cultural, ethnic, and religious backgrounds. In many verses, the holy Qur`an reminds about the unity of mankind and the necessity of their cooperation. Developing some theoretical principles to articulate and sustain foundations for such unity is of a great value, not only to the multiethnic and multicultural societies, but also to the entire global community. The religious heritage, especially the great legacy of Islamic civilization, can provide useful guidelines on this matter. This article investigates fundamentals of unity in multicultural society, based on Prophet’s Farewell Address, which delivered in a great gathering of companions (sahabah) during Prophet’s final pilgrimage to Makkah. Adopting the analytical method, the paper has derived from the Sermon eight principles as essential elements for unity in cultural diversity. It includes the principle of universal humanity, the principle of basic human rights, the principle of accountability and others. Although foundations of unity in multicultural society can be investigated empirically, however, the method adopted by this article was theoretical and analytic in nature. It analyzes the basic ideas of the above historic document to formulate the principles. Besides the Sermon, the religious texts (Qur`an and Sunnah) which related to unity of mankind, peace and harmony are analyzed. The paper has concluded that a careful study and wise application of the identified principles of unity is essential for effective management of multicultural societies to create harmony and peace to improve the quality of life.